Social Media Exposure and CrM Effects on Corporate Image via Attitude - Ferinda, Puspa; Thahirrah, Nadia Nur; Fachmi, Muhammad (Global Economic, Social, and Development Review, 2026)
Digital communication has become increasingly important for manufacturing companies, including those operating in the steel industry. Today, a company is not only evaluated based on the quality of its products or technical capability, but also on how well it communicates its social responsibility and builds positive relationships with its audiences. This study examines how Social Media Exposure and CrM (Cause-Related Marketing) influence Customer Attitude and Corporate Image in the context of Company X. The study used a quantitative approach by distributing an online questionnaire to audiences who had seen Company X’s social media content on Instagram, Facebook, and/or LinkedIn, were familiar with Company X, and had been exposed to its CSR-related content. The results show that CrM has a stronger role than Social Media Exposure in shaping Customer Attitude. In turn, Customer Attitude becomes an important pathway in building Company X’s Corporate Image. The findings also indicate that Company X’s CSR programs need to be more clearly connected to its core business as a steel manufacturing company, so audiences can better understand the relevance and social value of the programs. In addition, public awareness of Company X’s CSR activities remains limited. Therefore, Company X should communicate its CSR initiatives more consistently through social media and conventional B2B communication channels.